Echinodermata from Jørgen Brønlund Fjord, North Greenland. - Andersen, Max (Meddelelser om Grønland, 1971)
From Jørgen Brønlund Fjord, North Greenland (82°10'N, 30°30'W) 11 species of echinoderms are listed as the result of investigations during the Fourth P eary Land Expedition in the summer of 1966. One species is new to Greenland, viz. Myriotrochus eurycyclus HEDING.